Latitudinal gradients in seed predation persist in urbanized environments - Hargreaves, Anna L. (2024)
Urbanization is creating a new global biome, in which distant cities and suburbs often resemble each other more than the natural areas they replaced. But while urbanization can profoundly affect ecology at local scales, we know little about whether it disrupts macroecological patterns. Here, we test whether urbanization disrupts one of the world’s most intriguing macroecological 60 patterns: the increase in predation intensity from high to low latitudes. Using >56,000 standardized experimental seeds of two plant species, we compared seed predation in urbanized and natural areas across 14,000 km of latitude, spanning the Americas. In natural areas, predation on both seed types increased 5-fold from high latitudes to the tropics, one of the strongest latitudinal gradients in species interactions documented to date. Surprisingly, latitudinal gradients in predation were equally strong in urbanized areas despite significant habitat modification. Nevertheless, urbanization did affect seed predation. Compared to natural areas, urbanization reduced overall predation and predation by vertebrates, but did not affect predation by invertebrates in general and increased predation by ants. Our results show that macroecological patterns in predation intensity can persist in urbanized environments, even as urbanization alters the relative importance of predators and potentially the evolutionary trajectory of urban populations.